Factors Influencing Customers’ Satisfaction with Using Mobile Payment Applications - Paul, Deepa; Velmurugan, R (Indian Journal of Information Sources and Services, 2025)
This research seeks to determine the drivers of customer satisfaction with specific reference to ease of use, transaction time, security, availability and integration, and customer service on Mobile payment applications. Since advanced payment solutions are still in development, awareness of these elements is essential for improving user experiences and confidence. The study identifies the research areas that are still the subjects of discussion and debate, namely, personalization, multiple hardware support, and offline payment. In fulfilling these objectives, the study hopes to contribute some practical suggestions for enhancing consumer satisfaction that may help both business managers and policymakers realize the objective of financial inclusion for an increased number of people across different ages, genders, and geographical locations. Keywords: Merchant & Consumer Satisfaction, Mobile Wallets & Money Applications, Usability, Access to Basic Financial Services, and Safety & Security